The Development of YouTube Media in Madrasah Ibtidaiyah for Aqidah Akhlak Subject Viewed from the Aspects of Validity and Practicality - Lena, Lena; Hamzar, Afif; Febrianto, Rian (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to develop YouTube-based learning media for Aqidah Akhlak (Islamic Faith and Morality) subjects at Madrasah Ibtidaiyah (Elementary Islamic Schools) and to assess its feasibility in terms of validity and practicality. The background of this research is based on the still-dominant use of lecture methods and textbooks, which are less effective in attracting students’ interest in learning in the digital age. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consist of six material experts, two media experts, four Aqidah Akhlak teachers, and thirty third-grade students of Madrasah Ibtidaiyah. The data collection instruments were validity and practicality questionnaires, which were analyzed using descriptive quantitative methods. The results show that the developed YouTube media has an overall validity score of 2.75, categorized as Valid Without Revision (VTR). Additionally, the practicality test results indicate that the media is categorized as Very Practical, with a percentage of 94% from teachers and 95% from students. These findings indicate that the YouTube media is feasible and easy to use for teaching Aqidah Akhlak. This study contributes to the development of innovative digital learning media and supports the transformation of more interactive and contextual Islamic Education learning at Madrasah Ibtidaiyah.